Genetic deletion of Mmp9 does not reduce airway inflammation and structural lung damage in mice with cystic fibrosis-like lung disease - Wagner, Claudius; Balázs, Anita; Schatterny, Jolanthe; Zhou-Suckow, Zhe; Duerr, Julia; Schultz, Carsten; Mall, Marcus A. (International journal of molecular sciences, 2022)
Elevated levels of matrix metalloprotease 9 (MMP-9) and neutrophil elastase (NE) are associated with bronchiectasis and lung function decline in patients with cystic fibrosis (CF). MMP-9 is a potent extracellular matrix-degrading enzyme which is activated by NE and has been implicated in structural lung damage in CF. However, the role of MMP-9 in the in vivo pathogenesis of CF lung disease is not well understood. Therefore, we used β-epithelial Na+ channel-overexpressing transgenic (βENaC-Tg) mice as a model of CF-like lung disease and determined the effect of genetic deletion of Mmp9 (Mmp9-/-) on key aspects of the pulmonary phenotype. We found that MMP-9 levels were elevated in the lungs of βENaC-Tg mice compared with wild-type littermates. Deletion of Mmp9 had no effect on spontaneous mortality, inflammatory markers in bronchoalveolar lavage, goblet cell metaplasia, mucus hypersecretion and emphysema-like structural lung damage, while it partially reduced mucus obstruction in βENaC-Tg mice. Further, lack of Mmp9 had no effect on increased inspiratory capacity and increased lung compliance in βENaC-Tg mice, whereas both lung function parameters were improved with genetic deletion of NE. We conclude that MMP-9 does not play a major role in the in vivo pathogenesis of CF-like lung disease in mice.
Gesehen am 23.01.2023